2015
DOI: 10.11646/phytotaxa.192.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Curcuma arida and C. sahuynhensis, two new species from subgenus Ecomata (Zingiberaceae) from Vietnam

Abstract: Two new Curcuma species are described and illustrated from Vietnam. They are compared to their closest allies from subgenus Ecomata. Curcuma arida from Núi Chúa National Park, Ninh Thuận Province, is compared to Curcuma pambrosima and C. vitellina, while Curcuma sahuynhensis from Quảng Ngãi Province is compared to Curcuma xanthella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 9 publications
2
10
0
1
Order By: Relevance
“…Curcuma sahuynhensis differs from C. cotuana by its cream‐white to pale yellow prominently L‐shaped anther (Fig. 4D in Leong‐S kornic kova et al ). The distributions of these species are shown in Fig.…”
Section: Curcuma Cotuana Luu šKorničk and Hđtrần Sp Nov (Fig –2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Curcuma sahuynhensis differs from C. cotuana by its cream‐white to pale yellow prominently L‐shaped anther (Fig. 4D in Leong‐S kornic kova et al ). The distributions of these species are shown in Fig.…”
Section: Curcuma Cotuana Luu šKorničk and Hđtrần Sp Nov (Fig –2)mentioning
confidence: 99%
“…& N.S.Lý and C. sahuynhensis Škorničk. & N.S.Lý (Leong‐S kornic kova et al ) from Vietnam, and C. corniculata Škorničk. and C. flammea Škorničk.…”
mentioning
confidence: 99%
“…Recent extensive explorations of gingers in central Vietnam have led to description of numerous new Zingiberaceae (Leong-Škorničková and Lý 2010, Leong-Škorničková et al 2011, 2015a, b, Lý 2016, 2017a. An interesting species of Amomum with large yellow flowers and echinate fruits was collected during the fieldwork of the first author in 2010-2016 in protected forested areas in Quảng Ngãi province.…”
Section: Introductionmentioning
confidence: 99%
“…Leong-Škorničková & Lý, 2010;Leong-Škorničková et al, , 2011Leong-Škorničková et al, , 2015aLeong-Škorničková et al, , 2015bLeong-Škorničková & Lưu, 2013;Leong-Škorničková & Trần, 2013). To put novelties in Indochinese Zingiberales in a wider context, an introduction to the phytogeography of the region can be found in Averyanov et al (2003) and an introduction to the family Zingiberaceae can be found in Leong-Škorničková & Newman (2015), as well as in some of the papers cited above.…”
Section: Introductionmentioning
confidence: 99%